Epidemiology, Natural History, Risk Factors, and Prevention of Graves’ Orbitopathy - Bartalena, Luigi; Piantanida, Eliana; Gallo, Daniela; Lai, Adriana; Tanda, Maria Laura (Frontiers in Endocrinology, 2020)
GO is the most frequent extrathyroidal manifestation of Graves’ disease, although it may rarely occur in euthyroid/hypothyroid patients with chronic autoimmune thyroiditis. It is a relatively infrequent disorder, and men tend to have more severe ocular involvement at an older age. The prevalence of GO is lower than in the past among patients with recent onset Graves’ hyperthyroidism, and moderate-to-severe forms requiring aggressive treatments are no more than 5-6% of all cases of GO. After an initial inflammatory (active) phase and a phase of stabilization (plateau phase), GO tends to improve and eventually inactivates (inactive or burnt-out phase). Minimal-to-mild GO often remits spontaneously, but complete restitutio ad integrum almost never occurs when GO is more than mild. Several risk factors contribute to its development on a yet undefined genetic background. Cigarette smoking is the most important of them. Early diagnosis, control and removal of modifiable risk factors, early treatment of mild forms of GO may effectively limit the risk of progression to more severe forms, which have a profound and dramatic impact on the quality of life of affected individuals, and remain a therapeutic challenge, often requiring long-lasting and multiple medical and surgical therapies.